Photoionization spectra by intense linear, circular, and elliptic polarized lasers - Ooi, Chong Heng Raymond; Ho, W.; Bandrauk, A.D. (American Physical Society, 2012)
We study the characteristics of ionization rates of an atom by an intense laser field using an extension of Keldysh theory. High-order semianalytical expressions are obtained for linear, circular, and elliptically polarized fields. We compare the features of the new rates with Keldysh analytical results as functions of frequency and electric field strength. The directionality of photoelectron emissions is compared for elliptical, circular, and linearly polarized cases. Laser polarization has significant effects on the ionization spectra and directionality of photoelectron emission.